Preoperative systemic immune-inflammation index as a prognostic indicator for patients with urothelial carcinoma - Zheng, Jianxiong; Peng, Lei; Zhang, Shaohua; Liao, Haiyang; Hao, Jiayao; Wu, Song; Shen, Haili (Frontiers in Immunology, 2023)
Innovativeness: This groundbreaking study, underpinned by the principles of evidence-based medicine, is focused on patients with urothelial carcinoma (UC), encompassing both bladder cancer and upper tract urothelial carcinoma. It aims to scientifically assess the systemic immuneinflammation index (SII) as a prognostic marker for patient outcomes. While several prior investigations have explored the prognostic value of SII in other urological conditions, our research marks the first venture into its application for UC, rendering this an innovative exploration. Furthermore, our study is registered on the PROSPERO website, boasting a unique registration ID, which further underscores its novelty and originality.